Sistem Informasi Pembayaran SPP Berbasis Web untuk Meningkatkan Efektivitas Pengelolaan Keuangan di SMK Imtaq Darurrahim Jakarta - Ahmad Hudzaifah; Eflin Teresia; Shafa Salsabila (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The web-based Tuition Payment Information Ssistem is designed to enhance efficiency and transparency in financial administration management at SMK Imtaq Darurrahim Jakarta. This ssistem was developed to replace the manual payment process, which is prone to recording errors and late payments. With key features such as automatic payment recording, receipt printing, and transaction history, this ssistem allows students and administrative staff to access financial information more easily and in real-time. The methodology used in developing this ssistem is the waterfall method, which includes requirements analysis, ssistem design, implementation, testing, and maintenance. The ssistem is built using web-based technology with PHP, HTML, and CSS programming languages, and MySQL as the database storage.